Role of myeloid cell leptin signaling in the regulation of glucose metabolism - Sandra Pereira (Nature Portfolio, 2021)
Abstract Although innate immunity is linked to metabolic health, the effect of leptin signaling in cells from the innate immune system on glucose homeostasis has not been thoroughly investigated. We generated two mouse models using Cre-lox methodology to determine the effect of myeloid cell-specific leptin receptor (Lepr) reconstitution and Lepr knockdown on in vivo glucose metabolism. Male mice with myeloid cell-specific Lepr reconstitution (Lyz2Cre + Lepr loxTB/loxTB ) had better glycemic control as they aged compared to male mice with whole-body transcriptional blockade of Lepr (Lyz2Cre − Lepr loxTB/loxTB ). In contrast, Lyz2Cre + Lepr loxTB/loxTB females only had a trend for diminished hyperglycemia after a prolonged fast. During glucose tolerance tests, Lyz2Cre + Lepr loxTB/loxTB males had a mildly improved plasma glucose profile compared to Cre − controls while Lyz2Cre + Lepr loxTB/loxTB females had a similar glucose excursion to their Cre − controls. Myeloid cell-specific Lepr knockdown (Lyz2Cre + Lepr flox/flox ) did not significantly alter body weight, blood glucose, insulin sensitivity, or glucose tolerance in males or females. Expression of the cytokine interleukin 10 (anti-inflammatory) tended to be higher in adipose tissue of male Lyz2Cre + Lepr loxTB/loxTB mice (p = 0.0774) while interleukin 6 (pro-inflammatory) was lower in male Lyz2Cre + Lepr flox/flox mice (p < 0.05) vs. their respective controls. In conclusion, reconstitution of Lepr in cells of myeloid lineage has beneficial effects on glucose metabolism in male mice.